Pemberdayaan Masyarakat Melalui Pengelolaan Bank Sampah dalam Meningkatkan Ekonomi Keluarga di Kelurahan Setia Asih Kabupaten Bekasi - Hamdan Hamdani; Anggi Yus Susilowati; Ade Hidayat (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This research discusses community empowerment through the Setia Asih Waste Bank program. The purpose of this research is to find out how the process of community empowerment through Waste Bank management and Waste Bank's efforts to improve the economy of the customer's family. The research method used in this research is qualitative type with a descriptive approach with data collection techniques using observation, interview, and documentation methods. The results showed that community empowerment through waste banks was carried out through four stages, namely awareness, understanding, utilization, and use stages. Setia Asih Waste Bank is concluded to be able to empower the community so that waste bank customers who are members make profits from waste processing in the form of money, gold and groceries.